(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Building provides comfort, security, privacy and accommodation to occupant but adverse to this is incessant building collapse that claimed lives and properties of peoples in Anambra State. This study investigated the extent of compliance to training and motivation practices in building industry in Anambra State. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. A survey research design was adopted for the study. A total of 304 out of 1,240 construction workers in building industries that were registered with Ministry of Housing Anambra State were randomly sampled. A structured questionnaire was used to ascertain ratings of construction workers on extent of compliance to training and motivation practices in building industry. Three experts carried out face and content validations of the instrument. Cronbach’s alpha reliability test was used to determine the reliability of the instrument and the results were 0.76 and 0.76 for training and motivation practices. The result of the reliability test yielded a value of 0.76 for the entire items which shows that the instrument has a high internal consistency and therefore considered suitable for the study. Mean and standard deviation were used to answer research questions, while Analysis of Variance (ANOVA) was used to test the hypotheses. It was found out that training and motivation practices were mostly rated to moderate extent by the construction workers. It was recommended that human resource managers should strictly comply to training and motivation practices in building industries.